Gynaecological Endoscopic Surgical Education and Assessment. A diploma programme in gynaecological endoscopic surgery. (April 2016) - Campo, Rudi; Wattiez, Arnaud; Tanos, Vasilis; Di Spiezio Sardo, Attilio; Grimbizis, Grigoris; Wallwiener, Diethelm; Brucker, Sara; Puga, Marco; Molinas, Roger; O'Donovan, Peter; Deprest, Jan; Van Belle, Yves; et al.
Abstract: In recent years, training and education in endoscopic surgery has been critically reviewed. Clinicians, both surgeons as gynaecologist who perform endoscopic surgery without proper training of the specific psychomotor skills are at higher risk to increased patient morbidity and mortality. Although the apprentice-tutor model has long been a successful approach for training of surgeons, recently, clinicians have recognised that endoscopic surgery requires an important training phase outside the operating theatre. The Gynaecological Endoscopic Surgical Education and Assessment programme (GESEA), recognises the necessity of this structured approach and implements two separated stages in its learning strategy. In the first stage, a skill certificate on theoretical knowledge and specific practical psychomotor skills is acquired through a high stake exam; in the second stage, a clinical programme is completed to achieve surgical competence and receive the corresponding diploma. Three diplomas can be awarded: (a) the Bachelor in Endoscopy; (b) the Minimally Invasive Gynaecological Surgeon (MIGS); and (c) the Master level. The Master level is sub-divided into two separate diplomas: the Master in Laparoscopic Pelvic Surgery and the Master in Hysteroscopy. The complexity of modern surgery has increased the demands and challenges to surgical education and the quality control. This programme is based on the best available scientific evidence and it counteracts the problem of the traditional surgical apprentice tutor model. It is seen as a major step toward standardization of endoscopic surgical training in general.